The Influence of Family on the Sexual Behavior of Teenagers - Ustilaitė, Stasė (Acta Paedagogica Vilnensia, 2002)
The aim of this article is to show the influence of family on teenagers’ sexual activity. The research that is described in the article is based on the answers of 1046 students (432 boys and 614 girls) of 14-17 years old. This article deals with a problem on family and its influence on teenagers’ sexual behaviour. The author stresses that the lack of love and attention bad relations between the members of family force its daughters and sons to look for this outside their home. The influence of Westem way of living, the occupation of women makes this situation very complicated and on the other hand - attractive to scientific research. The research that is in short presented and described in the article shows that 73,8% teenagers felt deprivation of emotions in the family and it has a direct influence on their sexual activities. The teenagers who didn't like their parents had more sexual activities. This all shows that we are to be very attentive to the problems of family if we wish to form an intellectually and emotionally mature society. It is very important for the development of the values of teenager to identify him/herself with the person he/she respects. Our results showed that 25,9% of boys and 27,0% of girls do not treat their mothers as an example they would follow, 31,5% and 43,3% correspondingly – do not treat their fathers as an example as well to discuss sex issues. The lack of love, emotional contacts, attention to the actual problems of teenagers are very important to children. The research shows that only 27,2% of girls and 33,0% boys would like to have the same relations in their future families as they do have now. This lets the author to make the conclusion that the influence of family on forming sexual behaviour of teenagers is very important. It also shows that the distance between children and their parents is growing.
Keywords: Teenager; early sexual experience; influence of family; sexual behaviour.